Viral macro domains reverse protein ADP-ribosylation. - Li, C; Debing, Y; Jankevicius, G; Neyts, J; Ahel, I; Coutard, B; Canard, B (American Society for Microbiology, 2016)
ADP-ribosylation is a posttranslational protein modification in which ADP-ribose is transferred from NAD+ to specific acceptors to regulate a wide variety of cellular processes. The macro domain is an ancient and highly evolutionarily conserved protein domain widely distributed throughout all kingdoms of life, including viruses. The human TARG1/C6orf130, MacroD1, and MacroD2 proteins can reverse ADP-ribosylation by acting on ADP-ribosylated substrates through the hydrolytic activity of their macro domains. Here, we report that the macro domain from hepatitis E virus (HEV) serves as an ADP-ribose-protein hydrolase for mono-ADP-ribose (MAR) and poly(ADP-ribose) (PAR) chain removal (de-MARylation and de-PARylation, respectively) from mono- and poly(ADP)-ribosylated proteins, respectively. The presence of the HEV helicase incisdramatically increases the binding of the macro domain to poly(ADP-ribose) and stimulates the de-PARylation activity. Abrogation of the latter dramatically decreases replication of an HEV subgenomic replicon. The de-MARylation activity is present in all three pathogenic positive-sense, single-stranded RNA [(+)ssRNA] virus families which carry a macro domain:Coronaviridae(severe acute respiratory syndrome coronavirus and human coronavirus 229E),Togaviridae(Venezuelan equine encephalitis virus), andHepeviridae (HEV), indicating that it might be a significant tropism and/or pathogenic determinant.